The Oxford handbook of the Bible in China - Yeo, Khiok-Khng (Oxford handbooks online Religion, 2021)
This Handbook, comprises of forty-eight essays, showcases the Bible's translation, expression, interpretation, and reception in China over the last thirteen hundred years: 1) translation of the Bible into China's languages and dialects; 2) expression of the Bible in Chinese literary and religious contexts; 3) Chinese biblical interpretations and methods of reading; and 4) the reception of the Bible in the institutions and arts of China. Each essay, written by an expert, consists of a comprehensive yet concise treatment set in a historical frame on topics as wide-ranging as: the first Chinese Bibles, Chinese Nestorian Christianity, Bible of the minority nationalities, Sino-Christian theology, printed illustrations of the Gospel in China, the Bible and Chinese films, Chinese calligraphy and the biblical texts, Chinese Classics and the Bible, and Chinese society and politics.